Saccharin Extraction And Analysis Of Drug And Food Samples By Derivative Ultraviolet (UV) Spectrophotometry - Sarwendah Ratnawati Hermanto; Roto Roto; Agus Kuncaka (EKSAKTA: Journal of Sciences and Data Analysis, 2018)
Saccharin extraction and analysis of drug and food samples was investegated by spectrophotometry ultraviolet (uv) derivative method were studied. The saccharin extraction was carried out using solvent of ethanol/chloroform (2:8 v/v). The limit of detection (LOD) and limit of quantification (LOQ) of the proposed method were  0.50 ppm and 1.82 ppm for the second order and 0.47 ppm and 1.58 ppm for the fourth, while for the zero order were 2,75 ppm and 8,55 ppm. The calibration curve was linear in the concentration range from 20-100 ppm (R2= 0.996 for the second order and R2=0.997 for the fourth). The percent recovery of saccharin was in the range 95.20-104.40% for the second order and 97.20-102.40% for the fourth. The range of saccharin concentration (w/w) in drugs, candies and toothpaste for the fourth derivative were 1.39±0.02 mg/kg until 7.15±0.05 mg/kg, 0.21±0.01 mg/kg until 2.09±0.01 mg/kg, and 0.15±0.03 mg/kg until 0.63±0.04 mg/kg, respectively.